Hybrid Conflicts: Digital media as instrument for manipulating. What has it been like in Ukraine? - Sogorin, Andriy; Atamanenko, Ihor; Purnak, Viktor; Martynov, Ihor; Halukh, Oleksii (Espacio Abierto, 2026)
In hybrid wars, digital media have become a powerful political manipulator of consciousness, so a deep understanding of the mechanisms of such manipulation is a key task in finding ways to counteract it. The purpose of the article is to identify, classify and quantify the main manipulative techniques used in digital media in the context of a hybrid conflict (on the example of the Russian-Ukrainian war), as well as to assess the specifics of their use by various social networks. To that end, a content analysis of 2024 posts from the Facebook, X (Twitter), and TikTok platforms was conducted, categorizing the samples into pro-Russian and pro-Ukrainian sources. The results revealed a profound asymmetry: manipulative techniques were more widespread in pro-Russian sources, in particular dehumanization of the enemy, conspiracy theories and visual misinformation. TikTok was the most manipulative, with visual manipulation as the main tool of influence. It turned out that there is a stable negative correlation between trust in the source of information and the amount of manipulation. The results of the study confirm the systemic nature of the information operation and point to the need for a comprehensive response based on media literacy, support for independent media, international cooperation, and accountability of digital platforms.